In Search of Opportunities : How a More Mobile Workforce Can Propel Ukraine’s Prosperity (Vol. 1 of 2) : Summary Report - World Bank (Washington, DC, 2013)
Ukrainians do not move often, and when they do move, they don't necessarily go to areas with good jobs and high wages. Internal mobility is about half of what is expected when comparing Ukraine with other countries. The lack of mobility is remarkable, given the availability of more jobs and better wages in several Ukrainian cities. Too few people are taking advantage of economic opportunities, and as a result, Ukraine's structural transformation has stalled. This is a sharp contrast to many other countries in Eastern Europe, where the transition to a market economy has been accompanied by a shift from widely-dispersed industries to a concentration of capital and production in a few areas, and from low- to higher-productivity sectors. Labor has largely mirrored the movement of capital and production. In Ukraine, however, labor is not flowing as smoothly to areas of high production. This report examines the mobility of workers inside Ukraine and their willingness to physically relocate from one area or region to another in search of better economic opportunities. The report explores the patterns and trends of labor mobility in Ukraine as well as the drivers and constraints of that mobility, and derives policy implications from its findings. Second chapter of this volume offers evidence of how a mobile workforce benefits the economy. It shows how the economic transition in most of Eastern Europe has been accompanied by the significant concentration of capital and people in a few areas. This has not happened to the same extent in Ukraine. Third chapter shows that what little migration we see in Ukraine is not necessarily going to the leading regions. For internal migration to lead to growth and better living standards, workers have to move to the areas of the country where productivity and therefore, wages are high, and where unemployment is low. Third chapter more over examines the factors that prevent Ukrainians from moving. Fourth chapter offers recommendations for creating greater labor mobility in Ukraine. It explains how addressing the institutional bottlenecks that affect internal mobility will allow more people, especially the poor, to access better jobs, accelerating growth and enabling living standards to rise.